Ventajas y riesgos de la implementación de herramientas de inteligencia artificial en el sistema judicial ecuatoriano - Vallejo Aristizábal, Sandro Vinicio (2021)
The administration of justice confronts the challenge to satisfy adequately the needs of the population and the judicial system users. On the other hand, information and communication technologies, and specifically artificial intelligence, have proven to be useful tools in different legal systems, which could be replicated in the ecuadorian judicial system and contribute to its governance. This article reviews of literature of these aspects, the ethical risks and the areas of our judicial system in which they could be replicated